2007
DOI: 10.1002/eat.20379
|View full text |Cite
|
Sign up to set email alerts
|

The addition of a parent and clinician component to the eating disorder examination for children and adolescents

Abstract: Parent and clinician reports are particularly important when assessing children and adolescents with AN or EDNOS-R, but may be less critical for those with BN or EDNOS-BP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 17 publications
(10 reference statements)
4
39
1
Order By: Relevance
“…These findings support a growing body of research reflecting the importance of parental involvement and satisfaction in the treatment of children and adolescents with eating disorders (Bryant-Waugh, Turner, East, & Gamble, 2007;Couturier, Lock, Forsberg, Vanderheyden, & Yen, 2007;Honey, et al, 2008;Kerr & McIntosh, 2001;Loth, Neumark-Sztainer, & Croo, 2008;Rome et al, 2003;Wells & Sadowski, 2001). The results of this study also expand upon existing research by offering important information about the potential benefits of a support group to parents as part of comprehensive treatment of eating disorders in children and adolescents.…”
Section: The Parent Support Groupsupporting
confidence: 81%
“…These findings support a growing body of research reflecting the importance of parental involvement and satisfaction in the treatment of children and adolescents with eating disorders (Bryant-Waugh, Turner, East, & Gamble, 2007;Couturier, Lock, Forsberg, Vanderheyden, & Yen, 2007;Honey, et al, 2008;Kerr & McIntosh, 2001;Loth, Neumark-Sztainer, & Croo, 2008;Rome et al, 2003;Wells & Sadowski, 2001). The results of this study also expand upon existing research by offering important information about the potential benefits of a support group to parents as part of comprehensive treatment of eating disorders in children and adolescents.…”
Section: The Parent Support Groupsupporting
confidence: 81%
“…Also, there were no cases of bulimia nervosa among the participants. Previous stud-ies have shown that adolescents with bulimia nervosa tend to have higher scores on the EDE than adolescents with anorexia nervosa, 14 and even report more of their eating disorder symptoms than their parents, 15 so the results of this study are not generalizable to populations containing young people with a wider range of eating disorders.…”
Section: Methodological Considerationsmentioning
confidence: 62%
“…Couturier et al 15 added parental and clinician components to the standard EDE and found that adolescents with anorexia nervosa and other restrictive eating disorders scored significantly lower than their clinicians on all four subscales of the EDE and significantly lower than their parents on the Restraint and Eating Concern subscales. This was not the case with young people who had bulimia nervosa or other eating disorders that involved bingeing and/or purging.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary reports suggest that the addition of a parent-report component to the EDE can be clinically useful in addressing minimization of eating disorder psychopathology in youth. 40 Further, given the preliminary findings herein that these youth may gain less weight during treatment, increased attention to understanding and describing this group is needed.…”
Section: Discussionmentioning
confidence: 99%